Are rhinitis and Eustachian tube dysfunction associated in United States adolescents?. (April 2023) - Adams, Dara R.; Rowan, Nicholas R.; Lin, Sandra Y.; Pinto, Jayant M.; Roxbury, Christopher R.
Abstract: Objectives: Despite longstanding clinical gestalt of a relationship between rhinitis and Eustachian tube dysfunction (ETD), population-level evidence supporting this connection is lacking, particularly among adolescents. We aimed to investigate the association between rhinitis and ETD in a nationally-representative sample of United States adolescents. Methods: We performed cross-sectional analyses of 2005–2006 National Health and Nutrition Examination Survey data (n = 1955, ages 12–19). Rhinitis (self-reported hay fever and/or nasal symptoms in the past 12 months) was stratified as allergic (AR) or nonallergic rhinitis (NAR) based on serum IgE aeroallergen positivity. History of ear disease and procedures was recorded. Tympanometry was classified by type (A, B, C). Multivariable logistic regression was used to test the association of rhinitis and ETD. Results: Among US adolescents, 29.4% reported rhinitis (NAR 38.9%, AR 61.1%), and 14.0% had abnormal tympanometry. Adolescents with rhinitis were more likely to report a history of ≥3 ear infections (NAR: OR 2.40, 95% CI: 1.72–3.34, p < 0.001; AR: OR 1.89, 95% CI: 1.21–2.95, p = 0.008) and tympanostomy tube placement (NAR: OR 3.53, 95% CI: 2.07–6.03, p < 0.001; AR: OR 1.91, 95% CI: 1.24–2.94, p = 0.006), compared to those without rhinitis. There was no association between rhinitis and abnormal tympanometry (NAR: p = 0.357; AR: p = 0.625). Conclusion: NAR and AR are both associated with history of frequent ear infections and tympanostomy tube placement in US adolescents, supporting an association with ETD. This association is strongest for NAR, suggesting that specific inflammatory mechanisms may be involved in this condition and potentially explaining why traditional therapies for AR are largely ineffective for ETD.